SEX DIFFERENCES IN CARDIOMETABOLIC RISK FACTORS IN A TYPE 2 DIABETES POPULATION: AN INTERIM ANALYSIS OF THE TARGET-T2D STUDY IN MALAYSIA - Lim, Lee Ling; Hussein, Zanariah; Noor, Nurain Md; Samsuddin, Syahrizan; Foo, Siew-Hui; Bidin, Mohamed Badrulnizam Long; Yong, Sy-Liang; Bebakar, Wan Mohamad Wan; Ghani, Rohana Abdul; Mustafa, Norlaila; et al. (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES This study aimed to examine differences in the control and treatment of cardiometabolic risk factors between males and females with type 2 diabetes (T2D) in Malaysia. METHODOLOGY The TARGET-T2D study, an ongoing cross-sectional study (December 2021–June 2022), involves T2D adults treated with lifestyle modification with and without oral/injectable glucose-lowering drugs for ≥12 months in outpatient settings. We included 8 tertiary public hospitals in the Greater Kuala Lumpur region. In this interim analysis (13 December 2021–31 March 2022), we compared the attainment rates of ABC targets (HbA1c<7%, Blood pressure [BP]<130/80 mm Hg, LDL-Cholesterol <1.8 mmol/L) and use of cardiorenal-protective drugs (sodium-glucose co- transporter-2 inhibitors [SGLT2i], glucagon-like peptide-1 receptor analogues, renin-angiotensin system inhibitors [RASi], statins) by sex. RESULTS Among 2532 patients (mean HbA1c 8.2 ± 2.0%, mean body mass index 29.8 ± 6.4 kg/m2, 54.4% females), females were younger and less likely to smoke than males. Of the entire cohort, 99.5% were at ESC high-/very high cardiovascular risk categories, wherein 70.3% of females and 78.6% of males were at very high-risk (p<0.001). Compared with males, more females attained BP <130/80 mm Hg (68.8% versus 62.2%; p<0.001), but not LDL-cholesterol <1.8 mmol/L (21.8% versus 31.5%; p<0.001) and all ABC targets (5.2% versus 7.3%; p=0.040). Fewer females were treated with SGLT2i (37.9% versus 44.2%; p=0.002), RASi (63.0% versus 69.6%; p<0.001) and statins (87.8% versus 92.6%; p<0.001) than males. CONCLUSION In this very high-risk T2D group, more males attained optimal risk factor control than females. Health services and mechanistic research are needed to explain the differences in risk profiles and treatment patterns.